Semantic-Grammatical Features of The Work “Otamdan Qolgan Dalalar” By Togay Murad - L.Ibragimova (Zien Journals, 2022)
In this article we will talk about the semantic-grammatical features of the work” the fields left by my father". The head is explained by examples, focusing on the expression of the parts. The writer created a poetic style specific to the application of the head piece.
Keywords: fiction; poetics; syntax; linguistics